(untitled) (Research, Society and Development, 2023)
Objective: To describe the number and regional distribution of hospital admission authorizations (AIH), hospitalization costs, average length of hospital stay (LOS), and mortality related to Shoulder Arthroplasties (SA) funded by the Brazilian Unified Health System (SUS) from 2012 to 2021. Methods: An ecological time-series study was conducted using Datasus data related to SA (codes 04.08.01.005-3 and 04.08.01.004-5) between the years 2012 and 2021. Results: During the evaluated period, there were 7,340 AIH, with 58% classified as urgent, 34% elective, and 8% unidentified. The regional distribution of AIH was 55% for the Southeast, 20% for the South, 19% for the Northeast, 5% for the Midwest, and 1% for the North. The total expenditure was R 13,452,071.23, with an average cost per hospitalization of R 1,830.96 (SD 96.17). The average length of hospital stay was 7.3 days. The mortality rate was less than 0.01%. The total expenditure was R 7,349,277.01 in the Southeast, R 2,703,527.69 in the South, R 2,698,977.58 in the Northeast, R 598,579.30 in the Midwest, and R 101,709.65 in the North. The average cost per procedure was higher in the Southeast, amounting to R 1955.31, while the lowest was in the North, with R 1374.87. Conclusion: The present study aimed to highlight the economic impact of total and partial shoulder arthroplasties on the Brazilian Unified Health System, in order to guide policies regarding the procedure.